If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 8x + -9y + -5z = 16 Solving 8x + -9y + -5z = 16 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '9y' to each side of the equation. 8x + -9y + 9y + -5z = 16 + 9y Combine like terms: -9y + 9y = 0 8x + 0 + -5z = 16 + 9y 8x + -5z = 16 + 9y Add '5z' to each side of the equation. 8x + -5z + 5z = 16 + 9y + 5z Combine like terms: -5z + 5z = 0 8x + 0 = 16 + 9y + 5z 8x = 16 + 9y + 5z Divide each side by '8'. x = 2 + 1.125y + 0.625z Simplifying x = 2 + 1.125y + 0.625z
| 4sec^2x+2tan^2x-6=0 | | 7ln(3x+10)=42 | | 4x-5x=8x-9+11x | | 2*(7/2X) | | 3(3-x)=5(2x-7)+2 | | (-2/9)=4/a | | -9-6+3= | | 9(11-k)=9(x-5) | | r(6r+1)=12 | | 1/4x-1/6x=100 | | 59=-75 | | (5a-2b)+(3a-4b)=0 | | 8(w+3)+4=-7w+11 | | 90x+50=100x | | 4(5-x)=-4.9+2.1(6x) | | 5(x+1)-2(x-1)=12 | | -(v+9)+7=-7v-12 | | -15x+8=7-15x | | 9p+7=6+3(p-1) | | x=x^2+6x+15 | | 9q+7=6+3(p-1) | | 3x+7=-2x-23 | | Ln(3)+ln(2)=ln(x) | | -7(s+10)+11=-5s-6 | | 6y+10=4+6y+6 | | .55x=2 | | 24-8x=1-11x | | 4-2(3x-5)+x=7(1-3x) | | 1/3h+4=8 | | y=(x-4)/5 | | 3-2(x-1)+4x=5-(2-x) | | -2/3(6x-12y) |